ANALISIS WACANA KRITIS KOMUNIKASI VERBAL PADA DEBAT CALON GUBERNUR DAN WAKIL GUBERNUR JAWA TIMUR 2018 - Tri Suharto; Bambang Dwi Prasetyo; Maulina Pia Wulandari (Ilmu Komunikasi, FISIP Universitas Pasundan, 2020)
ABSTRACT This thesis discusses political debates at the regional level, especially in East Java Province in 2018. The focus of the study is the strengths and weaknesses of candidates in presenting an empirical data or facts as knowledge in argumentation. From these problems, this study uses a qualitative approach with critical discourse analysis methods to examine texts in depth. This research combines two theories, functional theory of political campaign discourse (attacks, acclaims, defenses) by W.L. Benoit and power & Knowledge by Michel Foucault. From the results of this study, candidate No.1 (Khofifah Indar Parawansa & Emil Elestianto Dardak) strongly gave an attack to candidate No. 2 (Saifullah Yusuf and Puti Guntur Soekarno) based on strong empirical data or facts, as a form of knowledge that gives the effect of power in argumentation (powerfull argumentation). But on the other hand, candidate No.2 not strong in making a defense from an opponent's attack. The weaknesses for candidate No.2 are judged by the lack of data or empirical facts used in argument, so that it gives the effect of a powerless argumentation